Estilo periodístico del diario digital la posta, caso ministerio de la muerte - Escandón Loor, Kerly Gabriela (2019)
The present research work was base on journalistic style that manages the digital newspaper La Posta, case ‘Ministry of Death’, with the aim of performing an analysis of the particular style that they possess. The techniques used were the observation of the médium, the lcdo. Luis Eduardo Vivanco made it posible to learn firsthand about the topic of interest. Throughout this case analysis the characteristics that conform to La Posta as a digital médium and in depth the particularitis of its style in general and in the objective case, the Minitry of Death as such, are exposed, the way in which they presented the reports and the events that tood place within the Ministry of Public Health by the person responsable at the time, María Verónica Espinoza, after the published investigations. La Posta as a digital newspaper is setting standards, and patterns within the new journalism in Ecuador, transcending in its journalistic processes, without leaving aside the investigative character; It was also confirmed that the journalistic style of the media is consistent with the personality of its journalists